Site-Specific Temperature Monitoring for Climate-Responsive Coastal Tourism Management at Mandalika Beach Club, Indonesia - Ika Umratul Asni Aminy; Rahmatun Inayah; Kormil Saputra (Tinta Emas Publisher, 2026)
Coastal destinations require site-specific weather information because visitor activities, service delivery, and outdoor operations are strongly shaped by local thermal conditions. This study examines the temperature characteristics of Mandalika Beach Club (MBC), Indonesia, as a coastal tourism activity space and evaluates the extent to which official BMKG data can represent the on-site thermal environment. Hourly field observations were collected from 8 July to 16 August 2025, producing 960 paired records with BMKG temperature data from the Lombok International Airport station. The data were analysed using descriptive statistics, temporal visualization, daily thermal indicators, and error metrics comprising mean bias error (MBE), mean absolute error (MAE), and root mean square error (RMSE). The results show that MBC was warmer on average than BMKG by approximately 1.22 °C, but it exhibited lower variability, with a standard deviation of 1.12 °C and an overall range of 6.88 °C compared with 2.91 °C and 13.00 °C in the BMKG dataset. The positive MBE of 1.21 °C indicates a persistent local warm bias, while the MAE of 3.24 °C and RMSE of 3.60 °C reveal substantial hourly discrepancies. These findings demonstrate that regional meteorological data are useful for general weather context, but they are insufficient as the sole basis for visitor-oriented thermal management at coastal tourism sites. The study contributes to tourism studies by translating microclimate evidence into practical implications for activity scheduling, shade planning, hydration provision, heat-risk communication, and climate-responsive destination management.